2021
DOI: 10.1128/msystems.01334-20
|View full text |Cite|
|
Sign up to set email alerts
|

Marine Community Metabolomes Carry Fingerprints of Phytoplankton Community Composition

Abstract: Phytoplankton transform inorganic carbon into thousands of biomolecules that represent an important pool of fixed carbon, nitrogen, and sulfur in the surface ocean. Metabolite production differs between phytoplankton, and the flux of these molecules through the microbial food web depends on compound-specific bioavailability to members of a wider microbial community. Yet relatively little is known about the diversity or concentration of metabolites within marine plankton. Here, we compare 313 polar metabolites … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 80 publications
12
43
0
Order By: Relevance
“…Advanced technologies such as ultrahigh resolution mass spectrometry enable detection of DOM composition at the molecular or compound level, in addition to specific biomolecules such as TDAA ( Sleighter and Hatcher, 2008 ; Lechtenfeld et al, 2014 ; Kido Soule et al, 2015 ; Medeiros et al, 2015 ; Osterholz et al, 2016 ). Using these techniques, metabolomics, including both particulate and dissolved metabolomics, has primarily been applied to marine culture studies ( Baran et al, 2010 ; Fiore et al, 2015 ; Longnecker et al, 2015 ; Kashfi et al, 2020 ), with more limited applications to field samples ( Durham et al, 2019 ; Johnson et al, 2020 ; Boysen et al, 2021 ; Heal et al, 2021 ). However, seasonal changes of dissolved metabolites in the marine environment are rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced technologies such as ultrahigh resolution mass spectrometry enable detection of DOM composition at the molecular or compound level, in addition to specific biomolecules such as TDAA ( Sleighter and Hatcher, 2008 ; Lechtenfeld et al, 2014 ; Kido Soule et al, 2015 ; Medeiros et al, 2015 ; Osterholz et al, 2016 ). Using these techniques, metabolomics, including both particulate and dissolved metabolomics, has primarily been applied to marine culture studies ( Baran et al, 2010 ; Fiore et al, 2015 ; Longnecker et al, 2015 ; Kashfi et al, 2020 ), with more limited applications to field samples ( Durham et al, 2019 ; Johnson et al, 2020 ; Boysen et al, 2021 ; Heal et al, 2021 ). However, seasonal changes of dissolved metabolites in the marine environment are rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…This range is similar to that observed within a prior comparative study of the metabolomes of 12 distinct phytoplankton despite the use of different analytical platforms [172]. We observed that 31 and 77 features in negative and positive mode data, respectively, were present within multiple organisms, similar in size to previously reported work evaluating the core metabolome of phytoplankton [173]. Overall, untargeted features were primarily observed within samples belonging to a single organism.…”
Section: Taxonomy Is the Primary Driver Of Variability Within Untarge...supporting
confidence: 88%
“…Currently, our group is using environmental metatranscriptomics and metabolomics data to identify links between community composition and metabolite exchange across environmental nutrient gradients. Notably, over half of the >300 metabolites detected by Heal et al ( 21 ) could not be identified. It is likely that additional carbon-cycle-relevant currencies are within these unidentified molecules, and continued effort to identify these metabolites is critical.…”
Section: Bridging Model Systems and Field Observationsmentioning
confidence: 87%
“…We then bioinformatically inferred metabolic pathways and tracked sulfonate dynamics in natural microbial communities of the North Pacific ( 17 ). So far, field observations suggest sulfonate production in phytoplankton is regulated by both light and nutrient availability ( 17 , 18 , 21 ), ideas that we are exploring back in the lab.…”
Section: Bridging Model Systems and Field Observationsmentioning
confidence: 99%
See 1 more Smart Citation